Interactive Technologies as a Means to Improve the efficiency and Quality of the Educational Process - Kulieva Shakhnoza; Karimova Makhbuba (International Journal on Human-Computing Studies, 2021)
The article based on analyzing the efficiency of interactive technologies as a means to improve the quality of the educational process. As we know, today the use of interactive methods in the learning process is widely introduced. This requires the humanization, democratization, and liberalization of the learning process. In short, the center of the learning process should be the learner's personality and needs. The learning process needs to be focused on needs of learners. Personalized education serves as a driving force for the organization of student learning activities that fulfill their interests, needs, and wishes. Interactive methods aim to achieve high results in a short period of time, without exerting considerable and physical effort. Teaching theoretical knowledge to the learner, acquiring skills and competencies in specific activities, developing moral qualities, and controlling and evaluating the student's knowledge requires a great deal of skill and agility. The learner will be given the opportunity to engage in creative thinking through search, finding, and processing of textbooks, information resource centers, the Internet, various other sources, without the knowledge being readily available. It gives the teacher and the student a constant creative search, continuous development and self-improvement.